PRESERVING PERSUASIVE MORAL MESSAGES IN CHILDREN LITERATURE - Ananda Firda Pratama; Uais Alqarnie Sayyidut Tabi’in; Sayla Nur Syahfah Ramadhani; Cahyaningsih Pujimahanani; Rommel Utungga Pasopati; Anicleta Yuliastuti (Jurnal Citra Multidisiplin, 2026)
This study examines how persuasive moral messages are preserved and communicated in children's literature. Although children's stories have long served as vehicles for moral education, little attention has been given to the specific narrative strategies that sustain persuasive moral elements within them. Using a qualitative textual analysis approach, this study analyzes selected children's stories to identify recurring moral themes and the persuasive techniques used to convey them. The findings reveal that moral values such as honesty, kindness, cooperation, responsibility, and perseverance are effectively communicated through character modeling, consequence-based storytelling, and emotionally engaging narratives. These strategies enable young readers to internalize moral lessons while remaining engaged with the story. This study concludes that preserving persuasive moral elements in children's literature is essential for supporting moral education and cultural value transmission across generations.